Concurrent versus sequential chemoradiotherapy for unresectable locally advanced stage III non-small cell lung cancer: Retrospective analysis in a single United Kingdom cancer centre. (2021) - Spencer, Alice; Williams, Jenna; Samuel, Robert; Boon, Ian S.; Clarke, Katy; Jain, Pooja
Highlights: Greater number of patients completed treatment in the CCRT arm versus the SCRT arm. No significant difference in survival outcomes when comparing CCRT and SCRT but local relapse rate was higher in the SCRT cohort. Higher rates of pulmonary toxicity and hospital admissions were seen in the CCRT versus SCRT treatment group. Low rates of 90-day mortality amongst both CCRT and SCRT treatment groups. Abstract: Introduction: : Stage III unresectable locally advanced non-small cell lung cancer (NSCLC) is a complex disease group with poor long-term survival. Clinical data suggests curative intent concurrent chemoradiotherapy (CCRT) is superior to a sequential (SCRT) approach but comes with additional toxicities. We report real world data regarding overall survival and toxicity to aid clinical decision making in balancing optimal management and treatment tolerability. Methods: : Retrospective analysis of survival data, treatment toxicities, and rates of treatment completion were performed for 241 patients who underwent chemoradiotherapy for unresectable stage III NSCLC within Leeds Cancer Centre from January 2011 to December 2014. Results: : Median survival was 18.8 months following SCRT compared to 22.7 months following CCRT HR 0.90 (95% CI 0.67–1.20, P  = 0.46). Median follow up was 21 months. The clinical benefit rate for CCRT compared to SCRT was 22.7% versus 24%. In the CCRT group 63.8% patients completed treatment compared to 46% in the SCRT arm ( P < 0.01). 90-day mortality rates were low in CCRT and SCRT cohorts at 4.3% and 1% respectively. There was greater pulmonary toxicity following CCRT versus SCRT (13.5% versus 1.0%, P  < 0.01). Conclusion: : This study provides real world data regarding the radical treatment of unresectable stage III NSCLC. Increased hospital admissions and pneumonitis toxicities did not adversely affect treatment completion for those undergoing CCRT; this was likely due to careful patient selection based on performance status. SCRT still remains an important treatment modality for patients who cannot tolerate the upfront CCRT approach but could still be treated with curative intent.